2022
DOI: 10.1097/prs.0000000000009231
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Pain Management in Cleft Lip and Palate Surgery: A Systematic Review and Meta-Analysis of Randomized Controlled Studies

Abstract: Background: Developing effective strategies to manage perioperative pain remains a focus of cleft care. The present study’s purpose was to systematically review perioperative pain control strategies for cleft lip and palate repair. Methods: A systematic review and meta-analysis of randomized controlled trials was performed. Primary outcomes included pain scale scores and time to analgesia failure. Cohen d normalized effect size permitted comparison between studies, and a fixed-effects model was used for anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 53 publications
1
16
0
Order By: Relevance
“…By comparison, in cleft lip repair bilateral infraorbital nerve blocks resulted in increased latency to first analgesia and decreased opioid consumption (P < 0.00001). Pfaff et al 28 reported significant improvements in pain control (P < 0.001) and time to analgesia failure (P < 0.001) using intraoperative nerve block compared with placebo in cleft lip studies. The authors similarly found improved time to analgesia failure (P < 0.005) using maxillary and palatal nerve blocks in palatoplasty studies.…”
Section: Pain and Analgesiamentioning
confidence: 99%
See 2 more Smart Citations
“…By comparison, in cleft lip repair bilateral infraorbital nerve blocks resulted in increased latency to first analgesia and decreased opioid consumption (P < 0.00001). Pfaff et al 28 reported significant improvements in pain control (P < 0.001) and time to analgesia failure (P < 0.001) using intraoperative nerve block compared with placebo in cleft lip studies. The authors similarly found improved time to analgesia failure (P < 0.005) using maxillary and palatal nerve blocks in palatoplasty studies.…”
Section: Pain and Analgesiamentioning
confidence: 99%
“…Many of the included studies investigated the use of various analgesia techniques that aimed at reducing postoperative opioid consumption. 2,[14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] Seven of the included studies investigated the effectiveness of bupivacaine for use in nerve block in cleft lip and/ or palate repair. 1,4,28,[30][31][32][33] All but 1 1 focused on infraorbital nerve block placement in cleft lip surgery patients.…”
Section: Pain and Analgesiamentioning
confidence: 99%
See 1 more Smart Citation
“…Preoperative optimization with a special focus on pain management has been a topic of interest of late. A recent review looked at 23 studies focusing mainly on the efficacy of intraoperative nerve blocks [6 ▪ ]. They found that infraorbital blocks with nasal blocks for concomitant cleft rhinoplasty led to less postoperative narcotic use and decreased hospital stay [6 ▪ ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent review looked at 23 studies focusing mainly on the efficacy of intraoperative nerve blocks [6 ▪ ]. They found that infraorbital blocks with nasal blocks for concomitant cleft rhinoplasty led to less postoperative narcotic use and decreased hospital stay [6 ▪ ]. To further explore perioperative pain control and narcotic minimization, an enhanced recovery after surgery (ERAS) protocol was implemented in 2020 in one Atlanta-based study.…”
Section: Introductionmentioning
confidence: 99%